INVESTIGATION ON DECISION SUPPORT SYSTEM (DSS) IN LEAN MANUFACTURING INDUSTRY FROM BEHAVIOR AND TECHNICAL ASPECTS - Muhammad Shafee, Nur Ain Qistina; Mohamad, Effendi; Muhammad Zaidi, Muhammad Khairul Hamizan; Abd Rahman, Mohd Soufhwee (Journal of Human Capital Development (JHCD), 2025)
In every industrial enterprise, choices are crucial since they may decide success or failure. Consequently, the decision-making process is crucial to lean production. However, further study is necessary to appreciate the relevance of Decision Support System (DSS) in the lean manufacturing business. This study exposes the classification of DSS, its range of applications, and suggestions for future research based on two key factors, namely, behavioral, and technological problems. This study makes considerable use of academic databases such as Scopus, Google Scholar, Emerald Science, and ResearchGate. In total, 50 papers have been identified. Each result, criterion, and categorization are supplied and classified. It is proved, from the literature treasure that DSS has the highest contribution on the Evaluation, 38%, following by, Mixed Application 26%, and others. Henceforward, this paper discussed the Behavior Aspects of users‘ confident, prejudice and discrimination issues, and customization. From the Technical issues, the discussion was on the technological capabilities, software language, parameters aggregate, user interface, market culture and social norm, giving out criticism for the future development of DSS-Lean, especially for the manufacturing industry. The authors believe that this study will lead the way for future research in the same field based on its primary findings. Keywords: decision support system, lean manufacturing, behaviors aspects, technical aspects